Ad fontes – terug na die Skrif, of na Jesus, of na die belydenis? - Wyk, D. J. C. van (HTS teologiese studies, 2004)
Ad fontes – back to Scripture, or to Jesus, or to Dogma? A critical approach to the New Testament, its origins, and the development of theological trajectories in the early Jesus movements have caused historians to look for the foundational authority beyond the biblical canon as the decisive authority of Christianity. Some have indicated Jesus as the primary authority for the earliest followers of Jesus. Others have identified doctrinal traditions as authoritative before the canon was finally established. This study challenges the church as institution to consider a foundational authority beyond the written and canonised Scripture as a normative source for Christian faith and life.